Carbapenem-resistant Acinetobacter baumannii outbreak at university hospital - Takagi, E.H. (Sociedade Brasileira de Microbiologia, 2009)
Nineteen clonally related imipenem-resistant Acinetobacter baumannii isolates were recovered from eight intensive care unit patients. All isolates harboured bla(OXA-51)-like β-lactamase genes and showed the absence of 22 kDa fraction in outer membrane porin profile analysis. It suggests a combination of two mechanisms as responsible for carbapenem–resistant phenotypes.